Visualization of knowledge graph transformation - Hauschwitz, Marek; Svátek, Vojtěch, 1967 prosinec 1.-; Dudáš, Marek; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis explores the implementation of a web-based visualization application designed to facilitate the exploration of RDF knowledge graphs. The core functionality of the application relies on the adaptation of ontology transformation patterns to the domain of knowledge graphs. These patterns are utilized to implement "semantic zooming," a technique that mitigates visual clutter by dynamically aggregating and simplifying the graph topology based on the user's navigational needs. The application was architected as a Single Page Application using the Javascript React.js framework, incorporating a client-side SPARQL engine to execute the transformations directly in the browser. To validate the usability of the application, it underwent user testing quantified by the System Usability Scale. The study yielded an average usability score of 67.5. The evaluation confirms that applying transformation patterns as a layer for semantic zooming is a feasible strategy for knowledge graph visualization, identifying specific areas for future optimization in the interaction between graph transformations and user interface controls.
Vedoucí práce: Vojtěch Svátek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: znalostní a webové technologie [obor dipl. práce]; diplomové práce; master's theses